MANDARIN, PUTONGHUA AND CHINESE DIALECTS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Despite the growth in popularity of Chinese medicine over recent decades, the westward transmission of Chinese medical knowledge continues to be hampered by a number of problems, including a low level of linguistic access to primary Chinese sources, a low level of translation, and a lack of a standardized English terminology.